2016
DOI: 10.1093/molbev/msw011
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Frequencies and Effects ofcis- andtrans-Regulatory Mutations Affecting Gene Expression

Abstract: Heritable differences in gene expression are caused by mutations in DNA sequences encoding cis-regulatory elements and trans-regulatory factors. These two classes of regulatory change differ in their relative contributions to expression differences in natural populations because of the combined effects of mutation and natural selection. Here, we investigate how new mutations create the regulatory variation upon which natural selection acts by quantifying the frequencies and effects of hundreds of new cis- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
208
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(227 citation statements)
references
References 76 publications
14
208
5
Order By: Relevance
“…To determine whether natural selection has impacted trans ‐regulatory variation affecting TDH3 promoter activity, we constructed models of neutral evolution using the effects of new mutations defined in prior work (Metzger et al. ). These mutations were generated with the mutagen EMS (Metzger et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether natural selection has impacted trans ‐regulatory variation affecting TDH3 promoter activity, we constructed models of neutral evolution using the effects of new mutations defined in prior work (Metzger et al. ). These mutations were generated with the mutagen EMS (Metzger et al.…”
Section: Resultsmentioning
confidence: 99%
“…These mutations were generated with the mutagen EMS (Metzger et al. ), which mimics the most common type of point mutation in yeast (Zhu et al. ) and the most common type of polymorphism found among natural yeast strains (G→A and C→T; MacLean et al.…”
Section: Resultsmentioning
confidence: 99%
“…Other experimental studies on yeast (Gruber et al. 2012; Metzger et al. 2016) showed that cis -regulatory mutations arose less frequently with more moderate effects on phenotypic trait than other type of mutations potentially explaining their higher contribution to adaptive divergence over a longer period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Cis -regulatory changes are expected to be important drivers of local adaptation (Wray, 2007), while trans -regulatory variation is considered more likely to be under purifying selection (Schaefke et al 2013 but see also Landry et al 2005 for discussion of cis–trans coevolution). Correspondingly, trans -regulatory polymorphisms tend to affect gene expression less strongly than cis polymorphisms, and their effects are more likely to be nonadditive (Zhang et al 2011; Gruber et al 2012; Schaefke et al 2013; Meiklejohn et al 2014; Metzger et al 2016). Nevertheless, work in multiple species has demonstrated an important role for both cis and trans polymorphism in shaping expression variation (Cubillos et al 2012; Meiklejohn et al 2014; Guerrero et al 2016), and the role of trans variation may have been underestimated due to the higher statistical power required to detect it (Mackay et al 2009; Clément-Ziza et al 2014).…”
mentioning
confidence: 99%